(untitled) (Journal of Parents and Teachers, 2013)
Interdisciplinarity, the use of ICT, and learning based on problem solving form the basis of the project “The Channel of Success: Motivation and self-improvement through English and Music in a disadvantaged environment.” This project was awarded a prize on the 28th edition of the Francisco Giner de los Ríos Awards for Improvements in Education Quality in the field of Secondary Compulsory Education. These prizes are awarded by the Spanish Ministry of Education, Culture and Sport, and the BBVA Foundation. This is an interdisciplinar project involving the subjects of English and Music, which consists on the creation of an educational channel in the popular web page of videos Youtube. This channel includes a series of songs and dialogues made by pupils from the Francisco Romero Vargas High School in Jerez de la Frontera, Spain, and deal with different aspects in relation to the contents of Music and English, teaching values and problem solving. The main aim of the project is to find ways to motivate and integrate pupils in a disadvantaged neighbourhood in the southern area of the city of Jerez by means of promoting interest in learning, the importance of education in life, and values such as respect, tolerance and companionship. In the following article we will describe the most relevant aspects of our experience, focusing on the development of the project and its achievements. The videos involved in the project can be visited on the following web page: http://www.youtube.com/user/cadialba